Health Disparities in Uterine Cancer: Report From the Uterine Cancer Evidence Review Conference. Issue 4 (10th April 2022) - Whetstone, Sara; Burke, William; Sheth, Sangini S.; Brooks, Rebecca; Cavens, Arjeme; Huber-Keener, Kathryn; Scott, Dana M.; Worly, Brett; Chelmow, David
Abstract : Evidence for health disparities in uterine cancer from the Uterine Cancer Evidence Review Conference is summarized. Abstract : The Centers for Disease Control and Prevention recognized the need for educational materials for clinicians on the prevention and early diagnosis of gynecologic cancers. The American College of Obstetricians and Gynecologists convened a panel of experts in evidence review from the Society for Academic Specialists in General Obstetrics and Gynecology and content experts from the Society of Gynecologic Oncology to review relevant literature, best practices, and existing practice guidelines for the development of evidence-based educational materials for women's health care clinicians about uterine cancer. This article is the evidence summary of the literature review of health disparities and inequities related to uterine cancer. Substantive knowledge gaps are noted and summarized to provide guidance for future research.